PSYCHOLOGICAL AND PEDAGOGICAL MANAGEMENT STUDENT ACTIVITY AS A FORM OF DEVELOPMENT SOCIALLY SIGNIFICANT QUALITIES STUDENTS ’PERSONALITIES - Reva, Yu.V. (Pedagogy of Higher and Secondary Education, 2007)
The article investigates the influence of psychological and pedagogical guidance of students’ activity in terms of developing qualities which are socially important for a personality.